Linewidth optimization in fiber grating Fabry–Perot laser - Hisyam, H.K.; Mahdiraji, G.A.; Abas, A.F.; Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd (Society of Photo-optical Instrumentation Engineers (SPIE), 2014)
Linewidth optimization of a fiber grating Fabry–Perot(FGFP) laser is performed numerically. In addition to the external optical feedback (OFB), the effect of temperature, injection current, cavity volume, gain compression factor, and external cavity parameters [i.e., coupling coefficient (Co) and external cavity length (Lext] on linewidth characteristics are investigated. The effects of external OFB and temperature on linewidth characteristics are calculated according to their effect on threshold carrier density (Nth). The temperature dependence(TD) of linewidth characteristics is calculated according to the TD of laser parameters instead of the well-known Pankove relationship. Results show that the optimum external cavity length (Lext) is 3.1 cm and the optimum range of operating temperature is within 2°C from the fiber Bragg grating (FBG) reference temperature (To). In addition, the antireflection (AR) coating reflectivity value of 1 × 10−2 is sufficient for the laser to operate at narrow linewidth and low fabrication complexity. The linewidth can be reduced either by increasing the laser injection current or the strength of external OFB level.